Analysis of Prospective Teachers' Abilities to Designing Artificial Intelligence-Based Learning Media - Nur Elisyah; Widya Widya; Nova Herliana Hasibuan; Dinda Adha Hutabarat (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
This research evaluates the capability of prospective teachers to design learning media that effectively incorporates Artificial Intelligence (AI). Conducted within the Mathematics Education Study Program at Malikussaleh University, the study highlights the significant role of AI in education during the Society 5.0 era, particularly in enhancing the quality of learning. Using a descriptive quantitative research method, data was collected through a questionnaire distributed to 60 students in the Mathematics Education Study Program. The findings clearly indicate that 33,33% of respondents fall into the medium ability category, while 53.33% are classified as high and 13.33% as very high in their ability to design AI-based learning media. These findings suggest that while a majority of prospective teachers demonstrate strong competencies in designing AI-based learning media, a notable 33,33% remain in the medium category and may require additional support. It is crucial to enhance skills in creating AI-based learning media to ensure that prospective teachers are well-prepared to address the challenges of education in the digital age. This research provides valuable insights into the abilities of prospective teachers and is expected to serve as a key reference for developing more effective training programs in the future.